High-performance liquid chromatography for the determination of oxymatrine content in radix Sophorae tonkinensis. (2015) - Shao, Changli; Du, Chuling; Du, Jingsheng; Xia, Xi; , Yinghong Huang; Cai, Yu; Huang, Zhihai
No abstract available